Implementation of Decision Support System with Simple Additive Weighting (SAW) Method for Determination of Social Assistance Recipients: A Case Study in Ciledug, Tangerang - Tengku Rafi Syahrial; Meyrson Agintha Sitepu; Satrio Santoso; Ali Mustofa Izzulhaq; Andreya Naufal Subagyo; Ati Zaidiah (PT FORMOSA CENDEKIA GLOBAL, 2026)
This can lead to dissatisfaction among the community and reduce the effectiveness of social assistance programs. This research aims to develop a Decision Support System (SPK) based on the Simple Additive Weighting (SAW) method to ensure a fairer, more objective, and efficient distribution of social assistance. The SAW method is used to assess aid recipients based on five main criteria, namely family income, number of dependents, home conditions, employment status, and age of the head of the family. Each criterion is weighted according to its level of importance, and the data obtained from the respondents is processed through a process of normalization and final score calculation to determine eligible beneficiaries. The implementation of this method in RT 02, RW 06, Ciledug, Tangerang City, showed a significant increase in the efficiency and accuracy of the selection of social assistance recipients.